Simpler and More Accurate: Weighing the Mercury in Electrolytic Cells by Radiotracer Dilution Method - Sugiharto Sugiharto; S.B. Santoso; G.B. Santoso (Atom Indonesia, 2010)
Weight of mercury in electrolytic cell of soda industry is usually measured gravimetrically, which is typical labor work in character. Error sources of the gravimetric method might have come from the fact that some mercury’s are usually trapped in the cell due to complicated structure of electrolytic cell. This cause unknown errors. In addition, formation of amalgam at the cathode may cause a further uncertainty in the measurement. Total error from gravimetric method is 4% on average. Radiotracer dilution method provides advantages either for simplification of procedure and reduction of measurement error. In this experiment radioisotope mercury 203Hg, which was prepared in nuclear reactor was used to examine 13 of 14 electrolytic cells of soda plant. Each electrolytic cell was designed containing approximately 700 kg inactive mercury. Before injection, the radioisotope mercury was mixed with non radioisotope mercury in a bath to obtain a suitable injection aliquots and standard references. Calibration curve, which was derived from two stage dilution processes taken from standard references, was used to examine degree of mixing between radioisotope and non radioisotope mercury and it was also used in weight calculation of non radioisotope mercury in electrolytic cell. Injection was carried out simply by pouring the injection aliquots into the flowing mercury at the inlet side of the cell. Mercury samples from the cells were extracted at regular time intervals and filled into vials for counting. This was done for the primary conformation of the completeness of mixing of the tracer with the non radioisotope mercury in each cell. When complete mixing is achieved, the unknown quantity of mercury in each cell was calculated based on mass balance principle. From the calculation the weight of mercury in each electrolytic cell was not the same and maximum error of measurement obtained from this method is 2.48 %. Compared to gravimetrically error mentioned above, it was clear that radiotracer dilution method gives better result in terms of higher accuracy and simpler procedure in measurement of the weight of mercury in electrolytic cells. Above all, this method is very suitable to be implemented in soda industry.Received: 20 November 2009; Revised: 31 August 2010; Accepted: 31 August 2010